URUD-AURANGZEB ALAMGIR'S RELIGIOUS SERVICES AS A FOUNDATION OF ISLAMIC SOCIETY IN SUB CONTINENT AN ANALYTICAL STUDY - Saima Shehzadi; Hashir Ashfaq (دی اسکالر)
Many critic observers have narrated about misconception of conservative behavior of Aurangzeb based on inaccurate evidence. For example, denigrators proclaim the Aurangzeb demolished certain temples without preannouncing. In reality He issued many orders in security of Hindu temples and granted compensation and allotted land to brahmans, so they could handle their expenditures. Some other asserts that Aurangzeb restricted many Hindu festivals and celebration of Eid and Muharram banned. Infact these all blams are groundless. Alamgir is one of the most hated men in India. He is remembered as a religious extremist who sought forcefully afflic Hindus. When Alamgir become king, the virtual and social condition of Indian society was very awful, atheistic activities, irrationality, gambling, farming of bhang, drinking and fornication were common. In these circumstances Alamgir proved himself and able Muslim administrator. Aurangzeb was potentially the most powerful and wealthist king of his day. His approximately 50 years monarch had an intense impact on the political topography of early modern inside and his inheritance. His orders were strict about religious affairs and local benefits although beneficiary is a Hindu. Alamgir worked for Renaissance of Islamic Era. And present two nation theory in the simplest way.